Einfluss von Dual-Tasking auf das Geradeaus- und Kurvengehen älterer Menschen - Gordt-Oesterwind, Katharina; Müller, Christina; Gerhardy, Thomas; Schwenk, Michael (Zeitschrift für Gerontologie und Geriatrie, 2019)
BackgroundWalking is not an automatic movement task but requires continuous attention resources. While walking and undertaking an additional task (dual tasking), gait changes occur which are associated with falls in older adults. To date, the evaluation of gait characteristics under dual task conditions is typically performed during walking straight ahead (SW); however, everyday life also requires more complex walking maneuvers such as walking in a curve (CW). Complex walking maneuvers may require higher attentional resources and thus might have a greater impact on the gait under dual task conditions.ObjectiveThe aim was to compare the gait characteristics under dual task conditions during SW and CW.Material and methodsIn 30 community-dwelling older adults (mean age: 71.6 ± 6.6 years) gait parameters including single leg support phase, velocity, cadence, step length and width were measured by electronic gait analysis (GAITRite®, CIR Systems Inc., Franklin, New Jersey, USA) during SW and CW under single and dual task conditions. For each gait parameter the relative change from single to dual task condition was calculated as dual task costs (DTC) and compared using paired t‑tests.ResultsFor the single leg support phase, velocity, cadence and step width, descriptive results showed increased DTC during CW (2.08-23.74%) as compared to SW (1.39-12.90%). For cadence (DTC: SW 6.81 ± 12.58%, CW 10.54 ± 13.46%, p = 0.026) and step width (DTC: SW −12.90 ± 18.01%, CW −23.74 ± 56.37%, p = 0.004) the differences were statistically significant.ConclusionThe relative decline in gait performance under dual task conditions is greater during CW than during SW. The results suggest that CW requires greater attentional resources as compared to SW. In turn, the risk of falling might be increased during CW under dual task conditions. The present findings may contribute to the development of new, ecologically valid assessment and training strategies taking complex walking maneuvers into account.